2000
DOI: 10.1103/physrevlett.84.2758
|View full text |Cite
|
Sign up to set email alerts
|

Fast Response and Temporal Coherent Oscillations in Small-World Networks

Abstract: We have investigated the role that different connectivity regimes play in the dynamics of a network of Hodgkin-Huxley neurons by computer simulations. The different connectivity topologies exhibit the following features: random topologies give rise to fast system response yet are unable to produce coherent oscillations in the average activity of the network; on the other hand, regular topologies give rise to coherent oscillations, but in a temporal scale that is not in accordance with fast signal processing. F… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
359
1
5

Year Published

2005
2005
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 540 publications
(374 citation statements)
references
References 30 publications
9
359
1
5
Order By: Relevance
“…Patterns of coherence were studied in HodgkinHuxley neurons (Lago-Fernandez et al 2000;Kwon and Moon 2002) and in networks of Hindmarsh-Rose neurons (Bucolo et al 2002). Synchrony (Masuda and Aihara 2004) and self-sustained dynamic activity (Roxin et al 2004) have been described in small-world network of leaky integrate-and-fire neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Patterns of coherence were studied in HodgkinHuxley neurons (Lago-Fernandez et al 2000;Kwon and Moon 2002) and in networks of Hindmarsh-Rose neurons (Bucolo et al 2002). Synchrony (Masuda and Aihara 2004) and self-sustained dynamic activity (Roxin et al 2004) have been described in small-world network of leaky integrate-and-fire neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Apparently, the loss of both small-world and scale-free characteristics has been linked to various brain disorders [283][284][285], suggesting that these properties of functional connectivity are important for brain operation. For example, it was shown that networks with smallworld characteristics are able to process information efficiently at both local and global levels [286], give rise to a fast system response with coherent oscillations [287], promote synchronized oscillations [288], allow both functional specialization and global integration, and maintain low wiring costs [281]. It is speculated that exactly these advantages might be the reasons for why these small-world and scale-free characteristics have evolved in the brain during the course of evolution [278].…”
Section: Eeg Functional Connectivitymentioning
confidence: 99%
“…In recent years, neuronal dynamics on complex networks, e.g., small-world (SW) ones [12], has actually become a focal research topic in theoretical neuroscience [14][15][16][17][18][19], and network topology could play vital role in neuronal synchronization or coding dynamics. In this work, we also address such issues by performing similar studies on SW networks.…”
Section: Resultsmentioning
confidence: 99%
“…For instance, Gaussian white noise can induce coherence resonance in FitzHughNagumo (FHN) and Hodgkin-Huxley (HH) neuronal models [4][5][6], Perc et al [7,8] showed that channel noise in coupled HH neurons can control the spontaneous spike regularity, and the effects of correlated noise on spike coherence and spike firing rate of coupled neurons have also been investigated thoroughly in various neuronal systems [9][10][11] by Kurths. On the other hand, due to the complex topological connections, real neuronal networks often exhibit small-world and scale-free features [12,13], so spatiotemporal dynamics on complex neuronal networks has attracted increasing attention [14][15][16][17]. In previous works, we found that spatial synchronization and temporal coherence, which are practically absent in regular networks, can be greatly enhanced by random shortcuts between the neurons [18][19][20].…”
Section: Introductionmentioning
confidence: 99%